2013
DOI: 10.1016/j.vaccine.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of recombinant poxvirus L1-protein to aluminum hydroxide/CpG vaccine adjuvants enhances immune responses and protection of mice from vaccinia virus challenge

Abstract: The stockpiling of live vaccinia virus vaccines has enhanced biopreparedness against the intentional or accidental release of smallpox. Ongoing research on future generation smallpox vaccines is providing key insights into protective immune responses as well as important information about subunit vaccine design strategies. For protein-based recombinant subunit vaccines, the formulation and stability of candidate antigens with different adjuvants are important factors to consider for vaccine design. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…although that has more recently been shown to be antigen specific. Studies with poxvirus L1-protein antigen in our laboratories demonstrated AH binding is important for immunopotentiation, 26 and others have reported similar observations with pneumococcal protein antigens. 27 The WHO recommends greater than 80% of the diphtheria and tetanus toxoids to be adsorbed to aluminum adjuvants.…”
Section: Nrrv Antigen-aluminum Adjuvant (Ah) Interactionssupporting
confidence: 59%
“…although that has more recently been shown to be antigen specific. Studies with poxvirus L1-protein antigen in our laboratories demonstrated AH binding is important for immunopotentiation, 26 and others have reported similar observations with pneumococcal protein antigens. 27 The WHO recommends greater than 80% of the diphtheria and tetanus toxoids to be adsorbed to aluminum adjuvants.…”
Section: Nrrv Antigen-aluminum Adjuvant (Ah) Interactionssupporting
confidence: 59%
“…These facts led us to examine the effect on the immune response by activating two TLRs; TLR3 and TLR9 using their synthetic agonists (synthetic double stranded RNA molecules and bacterial CpG DNA, respectively). While adjuvants are routinely added to inactivated or subunit vaccines to confer pre-exposure immunity [32] , [45] [47] , in the present study we co-administered the adjuvant with a live vaccine and examined it as a therapeutic/p.e. treatment.…”
Section: Discussionmentioning
confidence: 99%
“…110 For example, for a recombinant smallpox L1-protein subunit vaccine, binding of antigen to alum particles was required for optimal immune responses. 111 Phosphate buffer treatment, which changed the surface charge of the aluminum particulates from positive to negative prior to vaccination, disrupted protein binding and reduced serum IgG titers, leading to increased morbidity and weight loss (an indirect measure of disease state) upon vaccinia virus challenge.…”
Section: Nanoparticles Regulating Immunity At the Single-cell Levelmentioning
confidence: 99%